Effects of integrative simulation practice on nursing knowledge, critical thinking, problem-solving ability, and immersion in problem-based learning among nursing students. - Young A. Song (Korean Journal of Women Health Nursing, 2020)
Purpose: This study was conducted to investigate the effects of problem-based learning--integrative simulation practice (PBL-ISP) on nursing knowledge, critical thinking, problem-solving ability, and immersion among nursing students. Methods: The study used a nonequivalent control group post-test design. A PBL-ISP educational program was provided to the experimental group, and hands-on practice using a high-fidelity simulator (HFS) was administered to the control group. There were 42 subjects in the experimental group and 40 in the control group. Data were collected during the fall semester of 2019. Using SPSS for Windows version 23.0, data were analyzed in terms of frequency, percentage, mean, standard deviation, the chi-square test, t-test, and Pearson correlation coefficients. Results: Significant differences between the experimental and control groups were found in nursing knowledge (t=3.67, p<.001), critical thinking (t=3.40, p=.001), problem-solving ability (t=3.52, p=.001) and immersion (t=4.44, p<.001). Conclusion: PBL-ISP was more effective in improving nursing knowledge, critical thinking, problem-solving ability, and immersion than was hands-on practice using an HFS.